Effective Swallowing Rehabilitation Strategies in Patients with Multiple Sclerosis Suffering from Dysphagia; A Review of Literature - Shahryar Zainaee; Shima Rahmani; Hamide Ghaemi (Shiraz University of Medical Sciences, 2020)
Background: Multiple sclerosis (MS) is a disease of the central nervous system (CNS) which leads to various clinical signs and symptoms such as dysphagia. Given the prevalence and consequences of the disease, it is vital for patients with MS (PWMS) to be under medical supervision and receive specific care and services immediately. The present study aimed to comprehensively and inherently describe various SRSs and clarify the probable effects of each on the swallowing mechanism in PWMS suffering from dysphagia and to eventually answer the question: Which SRS(s) are effective on dysphagia in PWMS? Study design: This study is a literature review. Method: A search of the Web of Science, PubMed, and Science Direct databases was carried out for relevant studies published from 1990 to 2020 and written in English. The search resulted in 772 articles. Ultimately, 103 articles in total were selected for inclusion in the present study. Results: The clinical results show that using different SRSs in dysphagia management can help reducing dysphagia and the risk for aspiration. These approaches are classified in four categories: compensatory methods, stimulation techniques, exercises, and maneuvers. Conclusion: The current review reports the positive impact of SRSs such as electrical and sensory stimulation methods, maneuvers, and compensatory methods on dysphagia in PWMS. They can reduce the risk of aspiration for PWMS and, consequently, provide a better quality of life.